Whole genome sequencing reveals genetic diversity and heatstress adaptation in Nigerian indigenous chickens - Gheyas, Almas A.; Rachman, M.; Bamidele, O.; Dessie, Tadelle; Smith, J.; Hanotte, Olivier H. (Wageningen University & Research, 2022)
Poultry is a crucial sector for the livelihoods and food security of millions of people in Nigeria. Here we present the first large scale whole-genome sequencing analysis on Nigerian indigenous chickens from different agro-climatic conditions, investigating their genetic diversity and adaptation to tropical hotclimates. We observe a large genetic diversity but low levels of population differentiation. Selection signature analyses were performed to identify candidate genes in relation to heat-stress adaptation including those specific to extreme hot-humid or hot-arid conditions. These results have important implications for the conservation of genetic diversity and breeding improvement of chickens for thermo-tolerance.